2019
DOI: 10.1177/1040638719892953
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a double-antigen sandwich ELISA to identify Anaplasma marginale–infected and A. centrale–vaccinated cattle

Abstract: Bovine anaplasmosis is a worldwide infectious disease caused by the intraerythrocytic bacterium Anaplasma marginale, which is transmitted by ticks and fomites. A. centrale is a less virulent subspecies used as a live vaccine in cohorts of 8- to 10-mo-old calves that did not naturally reach enzootic stability. We developed 3 variants of a double-antigen sandwich ELISA (dasELISA) using a recombinant major surface protein 5 (MSP5) from A. marginale (dasELISAm) or from A. centrale (dasELISAc) or using MSP5 from bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Three proteins, major surface protein 5 (MSP5) of A. marginale, surface antigen 1 (SAG1) of Neospora caninum, and merozoite surface antigen 2c (MSA2c) of Babesia bovis were expressed in E. coli and purified by pseudo-affinity on a Ni +2 -NTA agarose column following the protocol descripted for MSP5 protein [30]. These proteins share the sequence (FKIEGRH HHHHH) in the C-terminal extreme with four of the proteins used as immunogens, and were used for the anti-His-tag adsorption step or for the determination of the presence of these antibodies at the post-absorption step.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…Three proteins, major surface protein 5 (MSP5) of A. marginale, surface antigen 1 (SAG1) of Neospora caninum, and merozoite surface antigen 2c (MSA2c) of Babesia bovis were expressed in E. coli and purified by pseudo-affinity on a Ni +2 -NTA agarose column following the protocol descripted for MSP5 protein [30]. These proteins share the sequence (FKIEGRH HHHHH) in the C-terminal extreme with four of the proteins used as immunogens, and were used for the anti-His-tag adsorption step or for the determination of the presence of these antibodies at the post-absorption step.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…Adicionalmente, se extrajeron muestras de sangre para serología de 20 vacas en cada establecimiento (E1 y E2), entre ellas la madre del ternero sometido a necropsia en E1. La presencia de anticuerpos específicos contra B. bovis y B. bigemina en estas muestras se determinó por la técnica de ELISA indirecto descripta por Echaide et al (2004), mientras que los anticuerpos contra A. marginale se determinaron por la técnica de ELISA de doble paratope (Sarli et al, 2019). Por último, se obtuvieron también extendidos de sangre periférica en nueve vacas del E1 y seis vacas del E2, los cuales se procesaron de igual forma que para los terneros (Benavides Ortiz et al, 2012).…”
Section: Materiales Y Métodosunclassified
“…With regards to tick vaccination, recent studies have shown that antitick recombinant vaccines such as aquaporin, subolesin, and tick gut glycoprotein Bm86 have a synergistic effect in reducing the engorgement of tick larvae in vitro [ 6 , 7 , 8 ]. So, an integral view of the tick-pathogen relationship should be considered to propose not only effective control measures but also successful diagnostic and vaccination methods as those recently reported [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%